Zero to One : Notes on Startups, Or How to Build the Future - Thiel, Peter and Masters, Blake (London Virgin Books, 2015)
"Thiel starts from the bold premise that we live in an age of technological stagnation, even if we're too distracted by our new mobile devices to notice. Progress has stalled in every industry except computers, and globalization is hardly the revolution people think it is. It's true that the world can get marginally richer by building new copies of old inventions, making horizontal progress from "1 to n." But true innovators have nothing to copy. The most valuable companies of the future will make vertical progress from "0 to 1," creating entirely new industries and products that have never existed before. Zero to One is about how to build these companies. Tomorrow's champions will not win by competing ruthlessly in today's marketplace. They will escape competition altogether, because their businesses will be unique. In today's post-internet bubble world, conventional wisdom dictates that all the good ideas are taken, and the economy becomes a tournament in which everyone competes to reach the top. Zero to One shows how to quit the zero-sum tournament by finding an untapped market, creating a new product, and quickly scaling up a monopoly business that captures lasting value. Planning an escape from competition is essential for every business and every individual, not just for technology startups. The greatest secret of the modern era is that there are still unique frontiers to explore and new problems to solve. Zero to One shows how to pursue them using the most important, most difficult, and most underrated skill in every job or industry: thinking for yourself"--Provided by publisher
Include Illustrations and Index
Keywords: New business enterprises -- New products -- Entrepreneurship -- Computer software industry